A Metallic Additively Manufactured Metamaterial for Enhanced Monitoring of Acoustic Cavitation‐Based Therapeutic Ultrasound. Issue 4 (13th December 2021) - Nie, Luzhen; Hutchins, David A.; Astolfi, Lorenzo; Cooper, Timothy P.; Clare, Adam T.; Adams, Chris; Watson, Richard L.; Thomas, Peter J.; Cowell, David M. J.; McLaughlan, James R.; Laureti, Stefano; Ricci, Marco; et al.
Abstract : The combination of ultrasound and microbubbles allows treatment of indications that would be impossible or too risk adverse with conventional surgery. During treatment, subharmonic and ultraharmonic components that can only be generated from microbubbles are of great interest for intraoperative monitoring. However, the microbubble emissions are several orders of magnitude lower in power compared to that of the fundamental frequency component from the ultrasound applicator, resulting in a low signal‐to‐noise ratio (SNR) for monitoring. A 3D acoustic metamaterial (AMM) immersed in water is proposed for suppressing unwanted ultrasound waves, which allows the improved sensitivity for detecting weak microbubble emissions. Numerically, the importance of shear waves on the AMM transfer properties is highlighted, though only longitudinal ultrasound waves are transmitted through water. Experimentally, the design is implemented in titanium using additive manufacturing, with an attenuation level of 40 dB at the fundamental frequency. Consequently, the application of the AMM efficiently improves the SNR for subharmonic and ultraharmonic microbubble emissions by 11.8 and 11.9 dB, respectively. The subharmonic components originally overwhelmed by noise are recovered. This is the first time that AMMs have been applied to passive acoustic monitoring and this work stands to improve treatment outcomes from cavitation‐mediated focused ultrasound therapy. Abstract : A metamaterial is proposed for passive acoustic monitoring for the first time. It requires no modification to the electronic hardware components and significantly improves the detection sensitivity of microbubble emissions. This work stands to improve cavitation‐based focused ultrasound therapy with enhanced intraoperative acoustic monitoring of the procedure.